The Effect of Humic Acids on Zymogenous Microbial Consortia Growth. Issue 9 (7th March 2014) - Miletić, Srdjan B.; Spasić, Snežana D.; Avdalović, Jelena; Beškoski, Vladimir; Ilić, Mila; Gojgić‐Cvijović, Gordana; Vrvić, Miroslav M.
<x xml:space="preserve">Abstract</x> This paper describes experiments with standard humic acids (HA‐S) and humic acids (HA) isolated from soil that was contaminated with mazut and treated with a consortium of microorganisms for the process of bioremediation (HA‐E). Both acids inhibited the toxicity of ferric chloride and increased the growth of a zymogenous microbial consortia compared with controls. Electron paramagnetic resonance spectroscopy showed that HA‐S and HA‐E exhibit high anti‐oxidative activity involving free radical scavenging and iron sequestration. HA additionally promote microbial consortium growth by providing protection from oxidative stress.